Electronic structure and catalytic study of solid solution of GaN in ZnO - Mapa, Maitri; Thushara, K. S.; Saha, Biswajit; Chakraborty, Purushottam; Janet, C. M.; Viswanath, R. P.; Nair, C. Madhavan; Murty, K. V. G. K.; Gopinath, Chinnakonda S. (Chemistry of Materials, 2009)
Solid solutions of GaN in ZnO (Zn1-zGaz)(O1-xNx) (x and z <= 0.15) have been prepared by simple solution combustion method, Except for minor changes in the lattice contraction, no significant change in the Wurtzite structure was observed. Raman and secondary ion mass spectrometry results show the direct Zn-N and Ga-N bonds in (Zn1-zGaz)(O1-xNx). Visible light absorption and XPS results demonstrate that N 2p states of nitride occupy the states above the O 2p valence band, and hence a change in optical band gap reduction occurs to similar to 2.5 eV from 3.37 eV for ZnO. Significant nitrogen fixation catalytic activity through NH3 formation has been observed at ambient pressure oil virgin (Zn1-zGaz)(O1-xNx) material, indicating its potential as a catalyst.